MOLECULAR DIAGNOSIS OF FUNGI CAUSING MELON CUCUMIS MELO L. ROOT ROT DISEASE, AND TESTING THE EFFICIENCY OF K2HPO4 AND TANNIC ACID IN INHIBITING THE FUNGUS RHIZOCTONIA SOLANI IN VITRO: MOLECULAR DIAGNOSIS OF FUNGI CAUSING MELON CUCUMIS MELO L. ROOT ROT DISEASE, AND TESTING THE EFFICIENCY OF K2HPO4 AND TANNIC ACID IN INHIBITING THE FUNGUS RHIZOCTONIA SOLANI IN VITRO (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study was conducted Plant diseases laboratory in the agricultural protection Directorate / Ministry of Agriculture for the purpose of molecularly diagnosing fungal isolates obtained by isolating them from different areas of melon Cucumis melo L. growing fields in Iraq and testing the chemical factors K2HPO4 and Tannic acid in inhibiting the growth of the fungus. The most pathogenic R. solani in the laboratory. The phenotypic diagnosis was confirmed by molecular diagnosis of isolates F8, F19, F23, F28, and F34 through polymerase chain reaction (PCR) technology for DNA amplification and nucleotide sequencing of the nitrogenous bases of the genetic material of the isolates. The electrophoresis results showed that bands with a molecular weight between 500 and 750bp were obtained, and the results of the nucleotide sequences of the nitrogenous bases of the genetic material of the isolates were F8 and F34, R. solani, F19, Fusarium oxysporium f.sp. ciceris, F23 Macrophomina phaseolina and semi fungs F28 Pythium aphanidermatum and have been registered in NCBI GenBank (National Center Biotechnology Information) under Accession numbers PP342522.1 (F8), PP342523.1 (F34), PP342524.1 (F19), PP342526. .1 (F23) and PP342527.1 (F28), and were compared with closely related global isolates recovered from GenBank. The isolates F8 and F34, R. solani, F19 is Fusarium oxysporium f.sp. ciceris and F28 Pythium aphanidermatum first registration in NCBI on Melon in Iraq. The results of testing different concentrations of K2HPO4 and Tannic acid showed that they inhibited the growth of the fungus R. solani. The concentrations were 10 g.100 ml-1 and 1.5 g.100 ml-1, respectively, completely inhibited the growth of the fungal colony. with a significant difference from the comparison treatment for both agents. It was noted that as the concentration of K2HPO4 and Tannic acid increased, the percentage of inhibition increased.